Simple Spectrophotometric Determination of Torsemide in Bulk Drug and in Formulations - Marothu Vamsi Krishna; Dannana Gowri Sankar (E-Journal of Chemistry)
A simple and cost effective spectrophotometric method is described for the determination of torsemide in pure form and in pharmaceutical formulations. The method is based on the formation of blue colored chromogen when the drug reacts with Folin-Ciocalteu (F-C) reagent in alkaline medium. The colored species has an absorption maximum at 760 nm and obeys beer's law in the concentration range 30 – 150 ug mL−1. The absorbance was found to increase linearly with increasing concentration of TSM, which is corroborated by the calculated correlation coefficient value of 0.9999 (n=8). The apparent molar absorptivity and sandell sensitivity were 1.896×103 L mol−1 cm−1 and 0.183 μg cm−2, respectively. The slope and intercept of the equation of the regression line are 5.4x10−3 and 1.00×10−4 respectively. The limit of detection was 0.94.The optimum experimental parameters for the reaction have been studied. The validity of the described procedure was assessed. Statistical analysis of the results has been carried out revealing high accuracy and good precision. The proposed method was successfully applied to the determination of TSM in pharmaceutical formulations.